2022
DOI: 10.3390/ma15031145
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Impact Strength of a Short Glass Fiber Compression Molded BMC by Shortening Fibers without Change in Equipment

Abstract: Bird strike, volcanic rock, hailstones, micrometeoroids, or space debris can cause damage to aircraft and space vehicles, therefore their composite materials must have high impact resistance to maximize safety. In a 55% wt. CaCO3 compression molded short glass fiber polyester GFRP-BMC (bulk molded compound), shortening the nominal 6.4 mm fiber length formulation, by 30 min extended mixing, to 0.44 mm was found to increase Charpy impact values, auc, without a change in the compression molding equipment. Specime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 29 publications
2
18
2
Order By: Relevance
“…However, counter to the results stated in the literature for numerous 2-phase fiber/polymer composite systems, in the 3-phase SGFRP-BMC, several mechanical properties have been increased by decreasing fiber length below that of commercially used samples [7,8,36]. For a widely-used compression-molded styrene butadiene SGFRP-BMC with 11 wt.% SGF and 55 wt.% CaCO 3 filler, it was found that shortening SGF length from nominal (commercial) 6.4 mm to submillimeter 0.44 mm raised impact strength 25% at the typically weak center of the mother panel [36]. Moreover, for an injection-molded styrene-butadiene SGFRP-BMC with 20 wt.% SGF, and 47.1 wt.% CaCO 3 filler, shortening SGFs from 6.4 mm to 0.44 mm increased tensile modulus 5 to 25% [8].…”
Section: Introductioncontrasting
confidence: 66%
See 4 more Smart Citations
“…However, counter to the results stated in the literature for numerous 2-phase fiber/polymer composite systems, in the 3-phase SGFRP-BMC, several mechanical properties have been increased by decreasing fiber length below that of commercially used samples [7,8,36]. For a widely-used compression-molded styrene butadiene SGFRP-BMC with 11 wt.% SGF and 55 wt.% CaCO 3 filler, it was found that shortening SGF length from nominal (commercial) 6.4 mm to submillimeter 0.44 mm raised impact strength 25% at the typically weak center of the mother panel [36]. Moreover, for an injection-molded styrene-butadiene SGFRP-BMC with 20 wt.% SGF, and 47.1 wt.% CaCO 3 filler, shortening SGFs from 6.4 mm to 0.44 mm increased tensile modulus 5 to 25% [8].…”
Section: Introductioncontrasting
confidence: 66%
“…Hence, in 2-phase fiber-polymer systems, mechanical properties typically decrease with a decrease in fiber length. However, counter to the results stated in the literature for numerous 2-phase fiber/polymer composite systems, in the 3-phase SGFRP-BMC, several mechanical properties have been increased by decreasing fiber length below that of commercially used samples [7,8,36]. For a widely-used compression-molded styrene butadiene SGFRP-BMC with 11 wt.% SGF and 55 wt.% CaCO3 filler, it was found that shortening SGF length from nominal (commercial) 6.4 mm to submillimeter 0.44 mm raised impact strength 25% at the typically weak center of the mother panel [36].…”
Section: Introductioncontrasting
confidence: 66%
See 3 more Smart Citations